Assessment of Antihypoxic Activity of S-analoges of Dihydropyrimidin-2-ones and Their Condensed Derivatives - N. A. Buzmakova; T. M. Zamaraeva; D. Yu. Ivkin; D. Yu. Apushkin; N. V. Slepova; N. V. Dozmorova (Разработка и регистрация лекарственных средств)
Introduction. Antioxydant activity, membrane stabilizing and cytoprotective effect of dihydropyrimidin analoges are widely described in various literary sources. One of the importantant mechanisms of action of antioxidants is their antihypoxic activity. It is the ability to increase tissue resistance to hypoxia. The search for drugs to increase the body's resistance under hypoxic conditions is an actual task in experimental and clinical pharmacology.Aim. Study of the antihypoxic activity of new S-analogs of dihydropyrimidin-2-ones and their condensed derivatives in various models of hypoxia.Materials and methods. 13 compounds S-analogs of dihydropyrimidin-2-ones and their condensed derivatives are objects of research. Their structure has been confirmed by spectroscopy methods. The antihypoxic activity was carried out by recommended methods for preclinical study of new pharmacological substances.Results and discussion. This paper presents the results of testing the obtained compounds of different structures on three models of hypoxia. The activity of a number of condensed tricyclic derivatives of dihydropyrimidine-2-thiones was studied in more detail using a model of acute normobaric hypoxia with hypercapnia.Conclusion. The compounds did not demonstrate high antihypoxic activity; some «structure-property» patterns were revealed.